Mitigating Salinity Stress in Brassica campestris (L.) Varieties by Rhizospheric Application of Potassium Nitrate - Nawaz, Rabia; Sohail, Shafaq; Hussain, Wajid; Razaq, Amara; Saeed, Imran; Maqbool, Sumrah (Indus Journal of Bioscience Research, 2025)
The motive of the study was to evaluate the effect of Potassium Nitrate (KNO3) on the plants which are under different levels of salt stress. Salt-induced stress is a common abiotic constraint hindering agricultural productivity, especially in salt-sensitive crops such as Brassica campestris L, used for extraction of valuable oil and biodiesel. Potassium Nitrate (KNO3) has potential to alleviate the adverse effects of salinity, particularly in the presence of Sodium Chloride stress is discussed in this paper. In a controlled pot trial, two different Brassica campestris cultivars Tori-7 (V1) and yellow mustard (V2), were applied with six experimental treatments with different concentrations of NaCl and KNO3. The parameters studied included secondary metabolite profiles that were fully evaluated in the study included alkaloids, flavonoids and phenolic compounds, in addition to yield attributes and measures of plant growth. As per the results, the accumulation of biomass, root and shoot elongation, vegetative development, and reproductive performance were significantly reduced by NaCl stress; the outcomes became worse with the increase in the amount of NaCl. In salty conditions, however, growth and yield parameters were augmented by the application of KNO3 in the rhizosphere, especially in V2 that was much more salt-tolerant than V1. Notably, the concentration of secondary metabolites showed a slightly different pattern; plants subjected to salt stress contained more of such compounds, and the content of alkaloid decreased after the addition of KNO3. The results support the notion that KNO3 enhances the capacity of Brassica campestris to resist salt and that it may be a viable agricultural management technique to reduce salinity stress and increase crop production in salty soils.